Tri Nga Moderation on the Influence of Tax Law Enforcement and Tax Morale on Regional Taxpayer Compliance - Sulistyawati, Ni Luh Gede Anggarayani; Diatmika, I Putu Gede; Sinarwati, Ni Kadek (Dinasti Publisher, 2025)
This study aims to analyze the influence of (1) tax law enforcement and (2) tax morale on regional taxpayer compliance, moderated by the understanding of Tri Nga. The population of this study consists of 13,736 regional taxpayers registered at Bapenda Badung Regency. The sampling technique used was purposive sampling, resulting in a sample of 383 taxpayers. Data was collected through the distribution of questionnaires. Data analysis was conducted using Moderated Regression Analysis with the help of the Smart PLS program. The results of the study indicate that both tax law enforcement and tax morale have a significant positive effect on regional taxpayer compliance. However, the understanding of Tri Nga does not strengthen the influence of either tax law enforcement or tax morale on regional taxpayer compliance.